Internal relative potency factors based on immunotoxicity for the risk assessment of mixtures of per- and polyfluoroalkyl substances (PFAS) in human biomonitoring. (January 2023) - Bil, Wieneke; Ehrlich, Veronika; Chen, Guangchao; Vandebriel, Rob; Zeilmaker, Marco; Luijten, Mirjam; Uhl, Maria; Marx-Stoelting, Philip; Halldorsson, Thorhallur Ingi; Bokkers, Bas
Graphical abstract: Created with BioRender.com Highlights: RPFs were derived for immune suppressive effects using available data in rodents and humans. RPFs were based on serum concentrations to allow interpretation of human biomonitoring data. Internal RPFs were successfully derived for eight PFAS based on rat lymphoid organ weights. Internal RPFs based on rat lymphoid organ weights are similar to those of rat liver weight. Abstract: Relative potency factors (RPFs) for per- and polyfluoroalkyl substances (PFAS) have previously been derived based on liver effects in rodents for the purpose of performing mixture risk assessment with primary input from biomonitoring studies. However, in 2020, EFSA established a tolerable weekly intake for four PFAS assuming equal toxic potency for immune suppressive effects in humans. In this study we explored the possibility of deriving RPFs for immune suppressive effects using available data in rodents and humans. Lymphoid organ weights, differential blood cell counts, and clinical chemistry from 28-day studies in male rats from the National Toxicology Program (NTP) were combined with modeled serum PFAS concentrations to derive internal RPFs by applying dose–response modelling. Identified functional studies used diverse protocols and were not suitable for derivation of RPFs but were used to support immunotoxicity of PFAS in a qualitative manner. Furthermore, a novel approach was used to estimate internal RPFs based on epidemiological data by dose–response curve fitting optimization, looking at serum antibody concentrations and key cell populations from the National Health and Nutrition Examination Survey (NHANES). Internal RPFs were successfully derived for PFAS based on rat thymus weight, spleen weight, and globulin concentration. The available dose–response information for blood cell counts did not show a significant trend. Immunotoxic potency in serum was determined in the order PFDA > PFNA > PFHxA > PFOS > PFBS > PFOA > PFHxS. The epidemiological data showed inverse associations for the sum of PFOA, PFNA, PFHxS, and PFOS with serum antibody concentrations to mumps and rubella, but the data did not allow for deduction of reliable internal RPF estimates. The internal RPFs for PFAS based on decreased rat lymphoid organ weights are similar to those previously established for increased rat liver weight, strengthening the confidence in the overall applicability of these RPFs.